RESEARCH ON FATIGUE CRACK GROWTH MODEL BASED ON HRR FIELD - LIU JianHui; XU JianPing (Jixie qiangdu)
Aiming at the safety and economic requirements in practical engineering,a type I fatigue crack propagation rate prediction model was proposed based on the Hutchinson-Rice-Rosengren(HRR)stress-strain field.The stress-strain distribution state of the crack tip region was described by the HRR stress-strain field,and a crack tip damage area was defined under the premise of considering the cyclic load and strain energy density theory.At the same time,in order to eliminate the problem of stress singularity value of the crack tip,a passivation radius calculation method considering the passivation effect of crack tip was established.Combining RICE′s plastic superposition method with plastic strain energy failure criterion,a type I fatigue crack propagation rate model was developed.The crack propagation rates of nine metallic materials were calculated using the proposed LIUX(HRR)prediction model,and the calculation results of the two crack propagation prediction models of Pandey(HRR)and CHEN-CAI Rice-Kujawski-Ellyin(RKE)were compared.At the same time,based on the different requirements of R2 fitting effect and fatigue crack propagation in the three stages,the scoring results of three prediction models were given,and corresponding scores were given from three aspects,safety,accuracy and economy.The final results show that the LIUX(HRR)prediction model in this paper has a wider scope of application,better fitting effect,and can better meet the needs of economy and safety in practical engineering.